Development and validation of a 3D-printed artificial round window niche for use in release kinetics analysis of round window niche implants (Transactions on Additive Manufacturing Meets Medicine, 2023)
The regular way to determine the in vitro release rates of drugs from implantable drug delivery systems consists of the complete immersion of the implant into a medium. The medium surrounds the implant, and the diffusion of the drugs occurs across the whole implant surface directly into the medium. This method does not accurately model the release rates if the real diffusion only happens across only one part of the surface of the implant, through a membrane, and into a small volume of medium. It also does not address the anatomical shape of the studied structure. One example for this is the insertion of an implant at the round window niche (RWN) in the middle ear, which enables the diffusion of drugs through the round window membrane into the inner ear. To solve this problem, we designed, three dimensionally (3D) printed and validated an artificial RWN (aRWN) to analyze the diffusion of dexamethasone from round window niche implants (RNI) into artificial perilymph over time. The aRWN consists of a human sized scala tympani with an opening at the apex and round window, respectively. We adjusted the model to be able to position an artificial membrane over the round window area and place a round window niche implant (RNI) on top of it. The scala can be filled with artificial perilymph which can be sampled via the opening at the apex. The established aRWN incorporates small dimensions, small liquid volumes, geometry, and the diffusion through a membrane into the results of release kinetics experiments. It allows better understanding of the diffusion rates of drug delivery implants for the treatment of inner ear disorders through the RWN and RWM.AcknowledgmentsWe thank Michaela Kreienmeyer and Tim Ehmann for the technical support.Author’s statementAuthors state no conflict of interest.
Keywords: 3D printing; release kinetics; release rates; inner ear therapies; 3D printed Implant; otolaryngology; round window niche; scala tympani; in vitro testing